O Saber e as escolhas alimentares de jovens: o entendimento da relação saúde-doença a partir da alimentação - Vasconcelos, Naiara Batista de (2019)
It is considered fundamental that school education can establish a relationship between what is learned in school and what is lived in daily life. Thus, biology teaching could significantly contribute to anticipating reflections on dietary trends that affect people's health and behavior, providing them with more knowledge conditions for making decisions with more autonomy and awareness. This study aimed to understand the motivations for students to make their choices about food, considering the relationship between nutrition and healthy life, according to the manifestations of knowledge learned in school about food and nutrition, focusing on issues of eating habits, styles of life and the influence of advertising and the media as possible motivating factors of food choices in their daily lives. Historically, the formation of the food standard of society has occurred amidst the necessary changes of adaptation to the lived world, according to Camozzi (2015), nowadays these changes can be strongly influenced by the technological advances in the food industry and globalization, whose attention and studies have occurred since a relationship between diet and some chronic no communicable diseases (NCDs) was established. As a methodological procedure, the research made use of quantitative and qualitative approaches, observation and dialogues with students to the application of questionnaires for data collection and descriptive analysis. The data set of the research, evidenced that there is a significant amount of conceptual knowledge among the research group, but this is not a determining factor for the food choice. The knowledge learned in school did not show a relation of influence when compared, for example, the influence of advertising and the media, which, on the contrary, presented a considerable factor influencing food preferences. It is possible that for the teaching of biology, in this presented context, the narrowing of scientific knowledge to the capacity to think for its own account and to decide for a food with less industrial process considering the possible impacts to its health still presents a long way. The study allows us to consider that the teaching of biology must find means that not only contribute to the acquisition of a theoretical knowledge, but that allows the student a level of awareness capable of stimulating him to think about the relation between his eating habits and the diseases related to chronic no communicable diseases, which are the main cause of death in the country.